Application of the Mamdani Fuzzy Logic Multi Output Method to Maintain Electrical Conductivity in Hydroponic Media for Lettuce (Lactuca sativa L.) and Bok Choy (Brassica rapa L.) - Nyi Mekar Saptarini; Mohamad Nurkamal Fauzan (Journal of Global Pharma Technology, 2020)
Nutrition in hydroponic cultivation affects the electrical conductivity (EC) that must be controlled to fulfill the plant’s requirement. The aim of this study was to determine the application of the Mamdani fuzzy logic with multi output to maintain the EC value, mixed volume in the tank and real time monitoring the current condition of the system. Case studies on lettuce (Lactuca sativa L.) and bok choy (Brassica rapa L.). The controlled system was NodeMCU and Arduino nano with analog pH, EC meter as input and pumps as an actuator. The results show that this application maintains an average EC value of 1.96 mS/cm and an average mixed volume of 53.4%. Plant conditions were sent to Android device in real time monitoring. The comparison data of manual and automatic (Mamdani fuzzy logic) monitoring were similar. Keywords: Lactuca sativa L., Brassica rapa L., Mamdani, multi output, real time monitoring